Results for Twin Singular Nonlinear Problems with Damping Term. (19th April 2011) - Zhang, Youwei
Abstract : By using the functional type cone expansion and compression fixed-point theorem in cones, some new and general results on the existence of positive solution for twin singular boundary value problems with damping term are obtained. An example is given to illustrate our results.